تحديات الانفتاح الاقتصادي وفرص بناء ميزة تنافسية مستدامة في المؤسسة الوطنية- دراسة حالة قطاع اقتصادي - ندى يحياوي; وسام لشقر (My University, 2022)
This study aims to identify the implications of Algeria's economic openness through the Euro-Mediterranean Partnership Agreement and the prospective accession to the World Trade Organization. In addition to many trends aimed at integrating into the international economy, Algeria has restructured its economy in line with the economic transformations in the international arena with a view to enhancing its economic competitiveness by providing an atmosphere conducive to the activity of its economic institutions in order to achieve a sustainable and effective competitive advantage, It is no secret that the many obstacles and challenges faced by these institutions and the developments associated with the phenomenon of market openness will be a cause of intensified competition and crisis in the competitive field. The need to strengthen their competitiveness and to seek opportunities to build competitive advantages that gain them superiority, Building on a research approach that blends descriptive and analytical approaches, the study found that most of the data on the subject showed that the steps achieved so far towards achieving economic openness in Algeria have not yielded the desired results, as its policies have not been accompanied by the preventive measures needed to meet the challenges of such openness. in particular as it relates to the preparation of national institutions for a decent competitive place in national and international markets, This failure may be linked mainly to the absence of a competitive business climate that opens doors and prospects for the sovereignty of national and international markets. in addition to national institutions' fear of exporting and not benefiting ......................................................... تهدف هذه الدراسة الى التعرف على تداعيات الانفتاح الاقتصادي الذي تعرفه الجزائر اليوم من خلال اتفاق الشراكة الاورو متوسطية وكذا الانضمام المرتقب لمنظمة العالمية للتجارة، بالإضافة إلى العديد من التوجهات الرامية للاندماج في الاقتصاد الدولي وفي هذا الصدد عملت الجزائر على إعادة هيكلة اقتصادها لتتماشى مع التحولات الاقتصادية التي تشهدها الساحة الدولية بهدف تعزيز تنافسيتها الاقتصادية عن طريق توفير جو ملائم لنشاط مؤسساتها الاقتصادية من أجل تحقيق ميزة تنافسية مستدامة فعالة، ولا يخفى لنا أن ما تواجهه هذه المؤسسات من عقبات وتحديات عديدة وتطورات مرتبطة بظاهرة انفتاح الأسواق سيكون سببا في اشتداد المنافسة و تأزم الوضع في الحقل التنافسي، مما يضعها أما ضرورة تعزيز قدراتها التنافسية والبحث عن فرص بناء مزايا تنافسية تكسبها خاصية التفوق عن غيرها، وبالاعتماد على منهج بحثي يمزج بين المنهج الوصفي والتحليلي توصلت الدراسة إلى أن جل المعطيات حول الموضوع بينت أن ما تحقق لحد الآن من خطوات نحو تحقيق الانفتاح الاقتصادي في الجزائر لم يأتي بثماره المرجوة إذ لم تترافق سياساته مع الإجراءات الوقائية اللازمة لمواجهة تحديات هذا الانفتاح، خصوصا فيما يرتبط بتحضير المؤسسات الوطنية لتكسب مكانة تنافسية لائقة لها في الأسواق الوطنية والدولية، ولعل أن هذا الفشل مرتبط أساسا بغياب مناخ أعمال تنافسي يفتح لها الأبواب والآفاق أمام سيادة الأسواق الوطنية وولوج الأسواق الدولية، بالإضافة إلى تخوف المؤسسات الوطنية من خوض غمار التصدير وعدم الاستفادة من الشراكات الأجنبية.